Conjugate heat transfer study of the impact of 'thermo-swing' coatings on internal combustion engines heat losses. (September 2021) - Broatch, Alberto; Olmeda, Pablo; Margot, Xandra; Escalona, Johan
To comply with the very strict emissions regulation the automotive industry is succeeding in developing ever more efficient engines, and there is scope for more improvements. In this regard, some investigations have suggested that insulating the combustion chamber walls of an internal combustion engine (ICE) yield low thermal losses. Most of the literature available on this topic presents simplified models that do not allow studying in detail the coating impact on engine efficiency. A more precise approach that consists in the combination of Computational Fluid Dynamics (CFD) and Conjugate Heat Transfer (CHT) simulations is used in this paper to predict the heat losses through the combustion chamber walls of a spark ignition (SI) engine. Two configurations are considered for the single cylinder engine: the metallic case and the same engine with coated piston and cylinder head. The insulation material has a low thermal conductivity ( k < 1.0 W /( mK )). The numerical results are validated by comparison with the results of a 1D heat transfer model and with experimental data for a medium load operation point (3000 rpm −7 bar IMEP). The solutions obtained are analysed in detail in terms of wall temperature distribution and heat transfer. The impact of the coating on the engine efficiency is thus assessed. The CFD-CHT calculations yields very good results in terms of heat transfer prediction during the whole engine cycle.